Gefühlte Unsicherheit: Deprivationsängste und Abstiegssorgen der Bevölkerung in Deutschland - Nadine M. Schöneck; Steffen Mau; Jürgen Schupp (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
– The question of what our economy and standard of living will look like in the future is a topic that concerns many today. This article deals with expectations for the future in the German population with regard to economic prosperity and social risks. It seeks to assess the prevalence of concerns about economic prosperity and fears of falling into precarious economic situations among the German population. To this end, various indicators of insecurity are used that measure, first, expectations of short-term social risks, and second, expectations of downward mobility. Moreover, the article addresses the deprivation anxieties and fears of downward mobility that have been claimed to plague the middle classes in Germany, and tests a hypothesis that has been put forward repeatedly in recent times: that "the middle" is suffering from increasing fears of declining social status. The analysis, which is based on data from the 2011 SOEP pretest, show large differences between current risk expectations and long-term fears of downward mobility: while the perception of short-term social risks is concentrated in lower income and status groups and decreases successively with increasing status levels, pessimism about the more distant future is much more widespread and does indeed impact negatively on segments of the social middle class. The results show that a substantial proportion of the population has lost faith in the idea of increasing prosperity and collective upward mobility.
Keywords: 330